The risk of demand shocks in dairy value chains in Uganda: Policy lessons from the COVID-19 crisis - Nabwire, Leocardia; Van Campenhout, Bjorn (International Food Policy Research Institute, 2022)
This policy note summarizes results of a study on the impact of COVID-19 on dairy value chains in Uganda. We use a stack survey consisting of 1616 dairy farmers, 695 small-scale milk traders, and 93 milk collection centers (MCCs) that were surveyed in-person in late 2018 as the basis for follow-up telephone interviews in 2020 and 2021. We find that the COVID-19 crisis mainly affected the dairy value chain through a reduction in demand as international trade reduced and households reduced consumption of more expensive foods due to income losses. As a result, prices drastically reduced at multiple stages of the value chain, and the number of actors affected by the price decrease worsened as the pandemic persisted. In general, we see that while dairy business closures during COVID-19 are limited, the joint reduction in demand and price leads to widespread reductions in scale of operation, dairy revenues and household income, although these somewhat recover over time, especially among MCCs. In the long-run, policy efforts to increase and stabilize local and export demand for dairy products seems most promising. For example, the government may institute policies that promote consumption of dairy products in schools and homes through information campaigns or temporary dairy vouchers. Government should also make it a priority to keep international trade flowing.